Ovariectomy and high salt increase blood pressure and alter sodium transport proteins in peripheral blood mononuclear cells of adult Wistar rats. Issue 10 (17th August 2021) - Vlachovsky, Sandra G.; Di Ciano, Luis A.; Oddo, Elisabet M.; Azurmendi, Pablo J.; Goette, Nora P.; Arrizurieta, Elvira E.; Silberstein, Claudia; Ibarra, Fernando R.
Abstract : New Findings: What is the central question of this study? In a model of salt‐sensitive hypertension in ovariectomized (oVx) adult Wistar rats, what is the expression of proteins related to sodium transport in peripheral blood mononuclear cells (PBMCs), and how does the response of proteins to high sodium intake compare with changes in blood pressure in intact female rats? What is the main finding and its importance? Sodium transport proteins in PBMCs react to high sodium and blood pressure markedly differently in oVx versus intact female rats. Protein expression shows sodium and pressure sensitivity. Renal immune cells increase in oVx under high salt. Abstract: Hypertension is a worldwide public health problem. High sodium consumption is associated with hypertension, and hypertensive mechanisms involve immunity cells. Peripheral blood mononuclear cells (PBMCs) are endowed with proteins related to sodium transport. We studied their abundance in PBMCs from intact (IF) or ovariectomized (oVx) adult Wistar rats under normal (NS) or high (HS) salt intake. Ovariectomy was performed at 60 days of life. At 145 days, one group of IF and oVx rats received NS or HS intake for 5 days. Another group of IF HS and oVx HS rats received hydralazine (HDZ) to reduce blood pressure (BP). Sodium balance and BP were recorded. Expression of Na +, K + ‐ATPase (NKA), Na + –K + –2Cl − cotransporter 1 (NKCC1), serum/glucocorticoid‐regulated kinase 1 (SGK1), dopamine D1 like receptor (D1DR), CD4 + and CD8 + were determined in PBMCs and CD45 + leukocytes in renal tissue. IF HS rats showed increased natriuresis and normal BP. NKA and CD4 + expression diminished in IF HS. Instead, oVx HS rats had sodium retention and high BP and increased the expression of NKA, NKCC1, D1DR, CD4 + and CD8 + in PBMCs. Renal CD45 + leukocytes increased in oVx HS rats. HDZ decreased BP in all rats. Upon HDZ treatment, NKA did not change, NKCC1 decreased in oVx HS rats, while SGK1 increased in both IF HS and oVx HS rats. Hormonal background determines BP response and the expression of proteins related to sodium transport in PBMCs and renal immune cells at HS intake. The analysis of NKA, NKCC1 and SGK1 expression in PBMCs differentiated salt‐sensitivity from BP variations.